2018
DOI: 10.3389/fcimb.2017.00540
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Microanatomy and Microbiota in a Rabbit Model of Rhinosinusitis

Abstract: Background: Rabbits are useful for preclinical studies of sinusitis because of similar physiologic features to humans. The objective of this study is to develop a rabbit model of sinusitis that permits assessment of microanatomy and sampling for evaluating shifts in the sinus microbiota during the development of sinusitis and to test how the mucociliary clearance (MCC) defect might lead to dysbiosis and chronic rhinosinusitis (CRS).Methods: Generation of CRS was accomplished with an insertion of a sterile spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 63 publications
5
49
1
Order By: Relevance
“…Differences could emerge when looking at an increased level of taxonomic resolution. Besides describing the baseline microbiome in rabbits, Cho et al found the genus Corynebacterium as a potential CRS-associated biomarker which is in accordance with results from human studies (13,89) . This shows that despite potential differences in basic microbial composition, putative disease-associated organisms remain similar.…”
Section: Advantages Limitations and Challengessupporting
confidence: 65%
See 4 more Smart Citations
“…Differences could emerge when looking at an increased level of taxonomic resolution. Besides describing the baseline microbiome in rabbits, Cho et al found the genus Corynebacterium as a potential CRS-associated biomarker which is in accordance with results from human studies (13,89) . This shows that despite potential differences in basic microbial composition, putative disease-associated organisms remain similar.…”
Section: Advantages Limitations and Challengessupporting
confidence: 65%
“…Despite the large variety of different rhinosinusitis models and their applications, only two studies to date have employed a model to study the sinonasal microbiota (10,89) . Microbial dysbiosis has been recently hypothesised to play a crucial role in the process of chronic mucosal inflammation (14) and a recent meta-analysis found that the bacterial community of CRS patients is significantly less diverse than that of healthy controls (13) .…”
Section: A Potential Model For Microbiome Researchmentioning
confidence: 99%
See 3 more Smart Citations